Kataster trójwymiarowy (3D) i numeryczne modele terenu w urządzaniu obszarów niezurbanizowanych - Wysocki, J.; Orlowski, P. (Видавництво Національного університету "Львівська політехніка", 2007)
The relief constitutes one of the main elements of information necessary for environment and civil engineering. Engineers dealing with construction of the country roads (expressway) railway location, storage tanks, power network and rural water supply systems etc. need information of the land relief . However design more often is recently carrying out using interactive methods, with consist in a collaboration of the man and computer, during the designing process. This requires digital map and digital land model (DTM). 11 can be performed by connection of 2D cadastral map with the DTM. In the paper are presented problem of getting digital terrain model for creation of the 3D cadastre.